Geoenvironmental study on solid waste landfill liner - Budihardjo, Mochamad Arief (Curtin University, 2015)
Hydraulic performance, physical deformation and GCL response to permeants were investigated using powdered and granular GCLs, bentonite and sand. Pollute v.7 simulated contaminant-transport through liner-system, showing ~70% decline in lead and chromium after permeating semi-permeable layer. Sludge improved bentonite subgrade shear stability. Carbon reduced sand subgrade’s shear strength, while slag and wood increased. Slag also increased sand layer’s liquefaction-resistance. Plaxis2D FEM model showed wavy ground-surface deformation in sand aquifer by groundwater extraction and dynamic/seismic loading.